Chapter The two versions of the life of Pope Sergius II in the Liber pontificalis. Anti-Frankish feeling in Rome after Louis II's expedition of 844 - Betti, Maddalena (Reti Medievali E-Book, 2022)
The analysis of the two versions of the life of Pope Sergius II (844-847) published by Louis Duchesne in his edition of the Liber pontificalis aims at identifying and discussing the tools developed by the Lateran to illustrate the relationship between the Apostolic See and Carolingian power at the time of the Emperor Lothair. I will first present the two versions of the life of Sergius and their circulation, then highlight the rhetorical strategies employed by the author to diminish the political significance of Louis II's journey to Rome (844). Secondly, I will refer to the second part of the so-called Farnesianus version of the life of Sergius II. In this particular section, the author, before the incomplete report of the Saracen raid on the mouth of the Tiber and the sack of St. Peter's Basilica (846), critically describes the pontificate of Sergius II, dominated by the negative figure of the pontiff's brother, Benedict, who imposed his tyranny over Rome and its territory on behalf of the emperor (most likely as a missus on the imperial side). In this regard, it is interesting to evaluate which are the concealed arguments introduced here to represent the alleged effects of the application of the Constitutio Romana (824) on the socio-political structures of the city and on the history of the Roman Church, to offer a hypothesis on the context of the composition of this version of the life of Sergius II. In particular, I will dwell on the denouncing of the simoniacal heresy, shown to be have been triumphant during the pontificate of Sergius II, as sign of the re-emergence in Rome of a theme particularly strongly felt among the Carolingian reformers, and one which can perhaps be most associated with the pontificate of Sergius' successor Leo IV (847-855).